2018
DOI: 10.3171/2018.3.focus1850
|View full text |Cite
|
Sign up to set email alerts
|

Tectal gliomas: assessment of malignant progression, clinical management, and quality of life in a supposedly benign neoplasm

Abstract: OBJECTIVETectal gliomas constitute a rare and inhomogeneous group of lesions with an uncertain clinical course. Because these supposedly benign tumors are frequently followed up by observation over many years, the authors undertook this analysis of their own case series in an effort to demonstrate that the clinical course is highly variable and that there is a potential for a progressive biology.METHODSCli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Pediatric TG should be considered a chronic disease, in which care for long-term morbidities is of paramount importance. Caregivers should be informed of the common long term morbidities in patients with TG including chronic headache, persistent visual symptoms and neurocognitive impairments [ 1 , 4 , 14 , 16 , 20 , 22 , 25 , 28 , 29 , 39 , 43 , 48 ]. Neuropsychologic assessments in our cohort suggested areas of deficit in working memory, processing speed and academics, specifically math, thus adding to prior reports of problems in visual attention deficits, behavior problems, and academic achievement, calling for neuropsychologic evaluation as standard of care in patients with TG [ 1 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric TG should be considered a chronic disease, in which care for long-term morbidities is of paramount importance. Caregivers should be informed of the common long term morbidities in patients with TG including chronic headache, persistent visual symptoms and neurocognitive impairments [ 1 , 4 , 14 , 16 , 20 , 22 , 25 , 28 , 29 , 39 , 43 , 48 ]. Neuropsychologic assessments in our cohort suggested areas of deficit in working memory, processing speed and academics, specifically math, thus adding to prior reports of problems in visual attention deficits, behavior problems, and academic achievement, calling for neuropsychologic evaluation as standard of care in patients with TG [ 1 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the psychosocial impact of this disease should not be underestimated. Mohme et al [11] assessed the quality of life in 12 TPG patients using the EORTC-QLQ-C30 and EORTC-QLQ-BN20 questionnaires and found that patients reported significant impairments in social, cognitive, and emotional functioning compared to healthy controls. They argue that these differences were probably mediated by the overall psychological sequels of the diagnosis rather than functional impairment caused directly by the tumor, supported by the fact that "future uncertainty" was documented in 18% of the interviewed patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to most of the other brain stem tumors, they show a benign and indolent clinical course. Therefore, they have been considered a distinct entity among glial brain stem tumors [5][6][7][8][9][10][11][12][13]. However, their location may lead to compression of the cerebral aqueduct and often results in secondary hydrocephalus.…”
Section: Introductionmentioning
confidence: 99%
“…Given the indolent nature of these tumours, observation may be an option in selected patients. However, therapeutic options including surgical interventions, systemic agents, and radiation therapy (RT) have been utilized for management of tectal gliomas as upfront or salvage therapies [2,3,[9][10][11][12][13][14][15][16][17]. Contemporary RT techniques and radiosurgery in the forms of Stereotactic Radiosurgery (SRS), Stereotactic Body Radiotherapy (SBRT) and Hypo fractionated Stereotactic Radiation Therapy (HFSRT) may be utilized for focused irradiation of several central nervous system disorders as well as tumours located throughout the human body .…”
Section: Discussionmentioning
confidence: 99%